Soap Bar Making from Waste Cooking Oil for Residents of 07 Area, Duri Pulo Sub-district, Jakarta - Pauhesti Pauhesti; Prayang Sunny Yulia; Harin Widiyatni; Yarra Sutadiwiria; Gabey Jane; Widia Yanti (International Journal Of Community Service, 2024)
Cooking oil that is no longer utilized can be used as a basic ingredient in the production of soap bar, and other products that can be used in daily life, such as washing clothes or kitchen utensils. The remainder of cooking oil, also known as waste cooking oil, is typically poured down the drain, where it can plug the drain since the oil freezes at low temperatures, causing environmental pollution. Based on this issue, the FTKE Universitas Trisakti community service team taught inhabitants of 07 Area, Duri Pulo Sub-district, Jakarta how to make bar soap from waste cooking oil. However, waste cooking oil cannot be used directly as an ingredient for creating soap because of the color and aroma, therefore it must be cleaned first by adding activated carbon, namely charcoal as an adsorbent, into the waste cooking oil to absorb the color and aroma. Later on, mix the oil and lye (a combination of NaOH and water), stir until the mixture resembles liquid soap, and then add around 1 ml of fragrance. Put the mixture in the drain. Leave the soap in the mold for 24 hours until it solidifies and hardens, then remove from the mold. It is intended that with this training, locals would be able to better their economic standing by saving more money while simultaneously helping to save the environment.